Resection of Locally Advanced Pancreatic Cancer after Neoadjuvant Chemotherapy with Modified FOLFIRINOX: A Prospective Phase II Study - Belluomini, Mario Antonio; Vasile, Enrico; De Lio, Nelide; Costa, Francesca; Cappelli, Carla; Campani, Daniela; Falcone, Alfredo; Boggi, Ugo (JOP. Journal of the Pancreas, 2013)
Context Twenty percent of the patients have a primary-resectable pancreatic ductal adenocarcinoma (PDAC) and in 30-40% surgery is denied because of local tumor growth in the absence of metastasis. These patients could be still considered for resection, if responsive to neoadjuvant chemotherapy. Objective We report the results of a phase II clinical trial, coupling high-dose multi-drug neoadjuvant chemotherapy with aggressive surgery. Methods All patients enrolled were selected by a multidisciplinary workgroup. Selection criteria: stage III locally advanced-PDAC (suspected arterial involvement), ECOG PS 0-1, age 18-75 years. A modified FOLFIRINOX regimen was used. Tumor response was evaluated according to RECIST. The opportunity to add a local treatment, either surgery or radiation-therapy, was evaluated after every CT follow-up. Results Between Nov 2010 and Nov 2012, 26 patients (mean age 59 years) were enrolled: 9/26 celiac axis involvement; 11/26 superior mesenteric artery; 6/26 celiac axis and superior mesenteric artery. Nine had a partial response (35%), 15 stable disease (58%), 2 progressed (8%). Fourteen (54%) underwent to surgery and 11 (42%) to resection with curative intent: 2 pancreaticoduodenectomies and 9 total-splenopancreatectomies. Mean-operative-time was 618 minutes. In-hospital mortality was 9%, overall-postoperative-morbidity 62%, surgical morbidity 12%, medical morbidity 50%. Mean hospital stay was 26 days. Eleven out of 11 were R0. Resected lymph-nodes mean number was 67 and nodal-metastasis mean number was 4. Twelve percent of resected venous segments and 33% of resected arterial segments were not involved on histology. Overall progression free survival was 17.6 months, resected patient progression free survival 17.8 months, out-of-surgery patient progression free- survival 10.3 months, and median overall survival 24 months. Conclusion The modified-FOLFIRINOX protocol in PDAC allows extended resection in a relevant percentage of stage III PDAC with results comparable to those in primary resectable patients. New data from further studies are needed before any final conclusion may be drawn.